O pensamento ético de Santo Anselmo de Cantuária : uma defesa do deontologismo mitigado - D’Oca, Fernando Rodrigues Montes (2014)
This work consists in a study on the ethical thought of Saint Anselm of Canterbury (1033-1109) and its goals are: (i) to show a systematic study on the Anselmian ethical theory, through the analysis of his major works which hold reflections of moral nature, as well as the main ethical concepts which emerge from these reflections; and (ii) to suggest an interpretation about the nature of Anselmian ethics, after an appropriate analysis of some interpretations that exist. Accordingly, this work is organized in three parts. The first part covers a study with the works which most directly include Anselm s ethical thought, such as: De Veritate (On Truth), De Libertate Arbitrii (On Freedom of Choice), De Casu Diaboli (On the Fall of the Devil) and Cur Deus Homo (Why God became Man). The second part explores the main concepts on which the Anselmian ethical theory bases itself on, such as: rightness (rectitudo), will (voluntas), and blessedness (beatitudo). Fundamentally, these two parts aim to accomplish goal (i). Finally, the third part faces the problem of Anselm s nature of ethics and, thus, aims to accomplish goal (ii). In this part, the major existent interpretations about the nature of his ethical theory are explicated, for instance: on one hand, the eudaemonist interpretations and, on the other, the deontologist interpretations. This part also includes a presentation of inconsistent and controversial points of these interpretations and, evidently, with the expound of our interpretation, which supports that the Anselmian ethical theory is of a deontological nature but its deontologism is not strong, because it coexists with some eudaemonist elements, and, therefore, defends that Anselm s ethical deontologism is mitigated.